Sarcocystis spp. of new and old world camelids : ancient origin, present challenges - Wieser, Sara Nathaly (2024)
Sarcocystis spp. are coccidian protozoans belonging to the Apicomplexa phylum. As with other members of this phylum, they are obligate intracellular parasites with complex cellular machinery for the invasion of host cells. Sarcocystis spp. display dixenous life cycles, involving a predator and a prey as definitive and intermediate hosts, respectively. Specifically, these parasites develop sarcocysts in the tissues of their intermediate hosts, ranging in size from microscopic to visible to the naked eye, depending on the species. When definitive hosts consume sarcocysts, infective forms are produced in the digestive system and discharged into the environment via feces. Consumption of oocyst-contaminated water and pasture by the intermediate host completes the parasitic cycle. More than 200 Sarcocystis spp. have been described to infect wildlife, domestic animals, and humans, some of which are of economic or public health importance. Interestingly, Old World camelids (dromedary, domestic Bactrian camel, and wild Bactrian camel) and New World or South American camelids (llama, alpaca, guanaco, and vicuña) can each be infected by two different Sarcocystis spp: Old World camelids by S. cameli (producing micro- and macroscopic cysts) and S. ippeni (microscopic cysts); and South American camelids by S. aucheniae (macroscopic cysts) and S. masoni (microscopic cysts). Large numbers of Old and New World camelids are bred for meat production, but the finding of macroscopic sarcocysts in carcasses significantly hampers meat commercialization. This review tries to compile the information that is currently accessible regarding the biology, epidemiology, phylogeny, and diagnosis of Sarcocystis spp. that infect Old and New World camelids. In addition, knowledge gaps will be identified to encourage research that will lead to the control of these parasites.